ASSESSMENT OF THE LOCAL EXPOSURE OF SKIN ON HANDS OF NUCLEAR MEDICINE WORKERS HANDLING 18F-LABELLED RADIOPHARMACEUTICALS: PRELIMINARY CZECH STUDY - Hudzietzová, J; Fülöp, M; Sabol, J; Doležal, Jiří (Radiation protection dosimetry, 2016)
The article summarises some preliminary results of the assessment of the exposure of hands of workers manipulating (18)F-labelled radiopharmaceuticals based on personal monitoring at two nuclear medicine clinics in the Czech Republic. The measurements were carried out using special thermoluminescence dosemeters the readings of which could be interpreted in terms of the personal dose equivalent Hp(0.07) approximating the equivalent dose to the skin at various locations on the surface of both hands. The results have shown that out of 21 workers monitored, ∼43 % (preparation and applications of radiopharmaceuticals) may reach an exposure equal to three-tenth of the annual dose limit to the skin. At the same time, it can also be concluded that in ∼10 % cases of workers, the relevant dose limit may be exceeded.
Keywords: radioizotopy fluoru; Hand; ruka; radioisotopová scintigrafie; Occupational Injuries; PET/CT; Skin; termoluminiscenční dozimetrie; kalibrace; ochranné rukavice; Gloves, Protective; pracovní úrazy; Positron Emission Tomography Computed Tomography; Radiopharmaceuticals; Calibration; Radiation Dosage; Radiation Dosimeters; Humans; nukleární lékařství; Fluorine Radioisotopes; Body Burden; monitorování radiace; kůže; Radiation Protection; lidé; pracovní expozice; Česká republika; Czech Republic; Radionuclide Imaging; dozimetry; radiofarmaka; Occupational Exposure; Nuclear Medicine; Thermoluminescent Dosimetry; radiační ochrana; Radiation Monitoring; obsah radioaktivních látek v organizmu; dávka záření